PENGEMBANGAN USAHA INTEGRASI SAWIT SAPI: DUKUNGAN LEGISLASI DAN STAKEHOLDER - Nyak Ilham; nFN Ashari; IGAP Mahendri; S. Wulandari (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2021)
The area of oil palm plantations is now reaching 14.7 million hectares, and it is an opportunity for Indonesia to develop an integrated beef cattle industry with the oil-palm integrated system. However, the development of this system is not yet massive. The problem among others is the plantation area owned by the smallholder farmers which is not sufficient for grazing area. To formulate concentrate feeds for the cattle, farmers need supports from palm oil processing companies for its raw materials. This paper is prepared as a literature review aimed at analyzing the prospects and constraints, legal aspects, and stakeholders' role in developing cattle-oil palm integration. This paper concludes that there is ample opportunity to develop an oil palm-cattle integration system. Furthermore, oil palm industry development requires legal aspects, the number of farmers and companies, and the organizations. A policy is needed to develop an oil palm-cattle integration system, coordinated by the Coordinating Ministry for Economic Affairs. The needed policies among others organizing smallholders involved in the integration system for easier access to technologies, extension, livestock health services, and access to feed raw materials such as palm kernel cake and sludge. Sustainability of oil palm-cattle integration efforts in the regions is needed to extend the status of current regulations regarding the integration system from Governor and Regency Regulations into Regional Regulations.